2018
DOI: 10.1097/01.aog.0000533328.55352.1b
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, and Pattern of LARC Use in Immediate Postpartum Period at Jimma University Medical Center, Ethiopia [18F]

Abstract: INTRODUCTION: Postpartum family planning (PPFP) is defined as the prevention of unintended pregnancy and closely spaced pregnancies through the first twelve months following childbirth. Immediate postpartum period is particularly favorable time to provide LARC methods and postpartum provision of LARC is safe and effective. Despite the advantages of LARCs, they are infrequently used in Ethiopia. METHODS: A cross-sectional study was conducted on 393 women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 0 publications
2
14
1
Order By: Relevance
“…(10.1, 15.5). This nding is lower as compared to study conducted in Jimma town, Western Ethiopia (53.2%) (15) and St. Paulo's hospital millennium medical college, Addis Ababa (45.5%) (40). This variation might be due to socio demographic, awareness difference, temporal difference of the study period and operational de nition of the outcome variable include less than one week of delivery as immediate postpartum period.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…(10.1, 15.5). This nding is lower as compared to study conducted in Jimma town, Western Ethiopia (53.2%) (15) and St. Paulo's hospital millennium medical college, Addis Ababa (45.5%) (40). This variation might be due to socio demographic, awareness difference, temporal difference of the study period and operational de nition of the outcome variable include less than one week of delivery as immediate postpartum period.…”
Section: Discussionmentioning
confidence: 61%
“…Research conducted in Jimma, west Ethiopia, showed that only 53.3% of women used the immediate postpartum family planning method used before discharge from the facilities (15) .variety of literature showed that the factors like marital status ,length of time after delivery , fear of side effect, ante natal care follow up, death of infant ,religion ,and lack of awareness were some of the factor affecting Postpartum family planning use among women in the immediate postpartum period (16,17).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The sample size was determined using single population proportion formula considering the following assumptions: the proportion of women who used longacting reversible contraceptives among immediate postpartum mothers was 53.2% (p=0.532), taken from a study conducted in Jimma Medical Center, with 95% CI at 1.96 and with margin of error of 5%. 5 Open access…”
Section: Sample Size Determination and Sampling Techniquementioning
confidence: 99%
“…The postpartum period is a critical time to address the high unmet need for FP and reduce the risk of short interpregnancies 2. Immediate postpartum family planning (IPPFP) refers to the provision of FP counselling and services as part of care to postpartum women within 48 hours after childbirth before discharge from the health facility 4 5. Increasing the accessibility of contraception methods among postpartum women is an important strategy because women may initiate sexual activity before obtaining FP methods at their 6-week postpartum visit 6 7…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that 12% of women who have delivered in a facility received postpartum family planning for the extended period until 12 months after delivery in eastern Ethiopia [11]. 22% of women received immediate postpartum-Introduce intrauterine devices (IUDs) in southern Ethiopia [20] and more than 45% of postpartum women received long-acting and reversible contraceptives (LARCs) in western and central parts of the country [21,22]. Within the national average of postpartum uptake, 8% of postpartum women received FP during the rst month of child birth and 21% of women received FP at six months.…”
Section: Introductionmentioning
confidence: 99%